2007
DOI: 10.1007/s00125-007-0897-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease is independently associated with an increased prevalence of chronic kidney disease and proliferative/laser-treated retinopathy in type 2 diabetic patients

Abstract: Aims/hypothesis Non-alcoholic fatty liver disease (NAFLD) is associated with an increased risk of cardiovascular disease in type 2 diabetes. Currently, there is a lack of information on associations between NAFLD and microvascular complications of diabetes. We assessed the associations between NAFLD and both chronic kidney disease (CKD) and retinopathy in a large cohort of type 2 diabetic individuals using a cross-sectional design.Methods Prevalence rates of retinopathy (by ophthalmoscopy) and CKD (defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
277
5
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(303 citation statements)
references
References 36 publications
14
277
5
7
Order By: Relevance
“…8,120,121 Emerging evidence also suggests that NAFLD is associated with increased risk of microvascular diabetic complications (i.e., chronic kidney disease and advanced diabetic retinopathy) in people with T2DM. [122][123][124] Overall, we believe that the strong link between T2DM and NAFLD supports more careful monitoring and evaluation of NAFLD among patients with T2DM.…”
mentioning
confidence: 71%
“…8,120,121 Emerging evidence also suggests that NAFLD is associated with increased risk of microvascular diabetic complications (i.e., chronic kidney disease and advanced diabetic retinopathy) in people with T2DM. [122][123][124] Overall, we believe that the strong link between T2DM and NAFLD supports more careful monitoring and evaluation of NAFLD among patients with T2DM.…”
mentioning
confidence: 71%
“…In the last 5 years, a number of cross-sectional community-based and hospital-based studies have consistently demonstrated that NAFLD, as diagnosed either by imaging [16][17][18][19][20][21][22][23][24] or by histology [25][26][27][28][29] , is associated with an increased prevalence of CKD (defined as presence of decreased estimated glomerular filtration rate [eGFR] or abnormal albuminuria or overt proteinuria) in patients with NAFLD. In these studies, the prevalence of CKD in patients with NAFLD ranged from approximately 20% to 55% compared to 5%-30% in those without NAFLD [16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Epidemiological Studies Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…In these studies, the prevalence of CKD in patients with NAFLD ranged from approximately 20% to 55% compared to 5%-30% in those without NAFLD [16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Notably, in most of these studies the association between NAFLD and CKD was independent of common cardio-renal risk factors across a wide range of patient populations.…”
Section: Epidemiological Studies Linking Nafld To Risk Of Ckdmentioning
confidence: 99%
“…In addition to emerging evidence that Mediterranean diets have a positive effect on cardiovascular epidemiology [8], a classical Mediterranean diet may be the ideal model for the prevention of diabetes [6] and its complications, including some consequences of non-alcoholic fatty liver disease, in type 2 diabetic individuals, such as chronic kidney disease and retinopathy [9].…”
Section: Modified Mediterranean Dietmentioning
confidence: 99%